[BP.05.05] COEXISTENCE OF SLEEP DISTURBANCES IN TREATED HYPERTENSIVE SUBJECTS - RESULTS OF POL-FOKUS STUDY. (September 2017) - Prejbisz, A.; Talarowska, P.; Klocek, M.; Gasowski, J.; Wolf, J.; Piotrowski, T.; Piotrowska, A.J.; Topor-madry, R.; Lesniak, W.; Czarnecka, D.; Kawecka-jaszcz, K.; Narkiewicz, K.; et al.
Abstract : Objective: To evaluate the overlap of sleep disorders - obstructive sleep apnoea (OSA) and insomnia and sleep habits (short sleep duration) and differences in clinical characteristics between patients with different sleep disorders in a large sample of patients with hypertension. Design and method: In a sub-study of the cross-sectional questionnaire-based observational Pol-Fokus study we included 3477 hypertensive patients attending a routine visit in primary or specialist care. To be included patients had to be >18 years old and had to be treated for at least 12 months with antihypertensive drugs. We defined hypertension control as blood pressure (BP) levels both < 140 mmHg/ < 90 mmHg. High risk of OSA was assessed on the basis of STOP-Bang questionnaire results. Insomnia was evaluated by means of Athens Insomnia Scale (AIS) and the patients with AIS score of 8 or more points were labeled as insomniacs. Short sleep duration was defined as usual sleep time < 6 hours. Cardiovascular (CV) risk was evaluated according to 2013 ESH/ESC guidelines. Results: Valid data on all three evaluated sleep disorders was available in 3241 patients (mean age 62.7 +/- 12.7 years; F 57.5%, M 42.5%). 47.1% of patients were free of any sleep disorder. Sleep disorders were presents with following frequency: high risk of OSA (17.6%), insomnia (13.5%), high risk of OSA and insomnia (10.2%), insomnia and short sleep duration (5.5%), all three (5.1%). Both insomnia and insomnia with short sleep duration were more frequent among women than men (20.7% and 9.3% vs. 4.5% and 0.5% respectively; p < 0.001). All sleep disturbances were characterized by lower rate of hypertension control as compared with patients without those disturbances. The lowest rate of HTN-control was evident in patients with all three disturbances. Coronary artery disease, cerebrovascular disease and high/very high CV risk were more frequent in patients with sleep disturbances with the highest rate in patients with coexistence of sleep disturbances. Conclusions: Our results showed that sleep disturbances and their coexistence are relatively common in treated patients with hypertension. Coexistence of those disturbances is related with worse blood pressure control and CV profile.